Kajian Teologis Transformasi Batiniah melalui Lensa Teologi Paulus: Dampak Praktis bagi Umat Kristen - Hesni Tandi Palloan; Melti Pakkun; Desti Randa Patandean; Joist Rama Karuru (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research aims to explore the concept of inner transformation in Paul's theology and analyze its practical impact on the daily lives of Christians. This study focuses on key verses in Paul's letters that describe the process of transformation of the heart and mind through faith in Christ. Through this approach, this research will also identify the real and concrete implications of Paul's theology in shaping the behavior and practical lives of Christians.